Imbibition behaviour and germination response in conventional and quality of Indian mustard (Brassica juncea) seeds - SWAMI, SUNIL; YADAV, SANGITA; YADAV, SHIV K; DAHUJA, ANIL; YADAV, DEVENDRA KUMAR (The Indian Journal of Agricultural Sciences, 2016)
Indian mustard [Brassica juncea (L.) Czern and Coss] seeds are well known for their multipurpose uses, such as oilseeds, spices etc. Being extensively cultivated in northern and western part of the country it constitutes major share in country’s oilseeds production. Developing cultivars having low erucic acid and glucosinolates (single zero and double zero) is a major objective of worldwide Brassica breeding. Such cultivars are also known as Quality Indian mustard. Seed; being vital input in agriculture, its quality determines the performance of a given genotype and efficiency of all other inputs too. Color variation among the seed coat is known to affect the rate of water uptake and thereby the vigor of seeds and these color variation is mainly because of pigments such as melanin and phenolics compounds. No such studies are reported in Indian mustard, though there is variability with respect to seed coat colour in both conventional and quality type of Indian mustard seeds. Thus the present investigation was carried out with a view to evaluate the imbibitional behaviour in black and yellow seeds of Indian mustard. The material had eight varieties of Indian mustard of which four genotypes each were of conventional and quality types. The seed of these genotypes varied for seed coat color, i.e. four black seeded and four yellow seeded genotypes. Thus, the material has two genotypes each with black and yellow seed coat from conventional and quality groups. We studied the rate of imbibition in black and yellow seeds and correlated them with the melanin and phenol content. We found that the black seeds were having higher amounts of melanin and phenol content and thus imbibing slowly than yellow seeds. On the other hand, faster imbibition in yellow seeds leads to imbibitional injury which is known to reduce the vigor in Brassica. Use of controlled deterioration revealed the proneness of yellow seeds to ageing and thus reduction in vigor of such seeds. Few yellow seeded cultivars showed resistance to such deterioration and thus could be used in improvement programme in Brassica.